The Efficacy and Safety of Biologic Drugs in the Treatment of Moderate–Severe Crohn’s Disease: A Systematic Review - Ana Avedillo-Salas; Sara Corral-Cativiela; Ana Fanlo-Villacampa; Jorge Vicente-Romero (Pharmaceuticals, 2023)
Conventional therapy is the most commonly used treatment for Crohn’s disease (CD), but it does not always achieve disease control, which is why the use of biologic drugs is increasing. The aim of this study was to analyze the efficacy and safety of biologic drugs in adult patients diagnosed with moderate–severe CD. An intensive search was performed in PubMed, Web of Science and Medline to collect phase 2 or 3 clinical trials published between 2018 and 2023 that were randomized, placebo-controlled and double-blind trials analyzing the efficacy and safety of biologic drugs in adult patients diagnosed with CD. This systematic review was conducted according to the PRISMA statement. Thirteen clinical trials evaluating eight biologic drugs were included. Upadacitinib, vedolizumab, adalimumab, guselkumab, mirikizumab, ustekinumab and risankizumab showed statistically significant efficacy across different clinical, endoscopic, histological, genetic, biomarker or quality-of-life parameters. However, PF-00547659 only showed statistically significant results for the CDAI-70 at week 12. In terms of safety, the incidence and severity of adverse effects were analyzed, with all drugs being well tolerated and presenting a good safety profile since most adverse effects were mild. Biologic drugs can be considered an effective and safe option for the treatment of moderate–severe CD in adult patients with an inadequate response or intolerance to conventional therapy.